Principles and applications of electrical engineering - Rizzoni, Giorgio (McGraw Hill Education, 2022)
Principles and Applications of Electrical Engineering provides an overview of the electrical engineering discipline specifically geared toward non-electrical engineering students. The hallmark feature of the text is its use of practical applications to illustrate important principles. The applications come from every field of engineering and feature exciting technologies. The principal objective of the book is to present the principles of electrical, electronic, and electromechanical engineering to an audience of engineering majors enrolled in introductory and more advanced or specialized electrical engineering courses. A second objective is to present these principles with a focus on important results and common yet effective analytical and computational tools to solve practical problems. Finally, a third objective of the book is to illustrate, by way of concrete, fully worked examples, a number of relevant applications of electrical engineering. These examples are drawn from the authors' industrial research experience and from ideas contributed by practicing engineers and industrial partners.